Respuesta :

Answer:

See explanation

Step-by-step explanation:

The question is not properly presented; I will answer this with the following similar question.

[tex]h(x) = -\frac{1}{3}x^2 + 4[/tex] --- [tex]x \ne 2[/tex]

[tex]h(x) = -4[/tex] --- [tex]x= 2[/tex]

Required

[tex]h(-5)\ \&\ h(2)[/tex]

Calculating h(-5)

This implies that: x = -5

[tex]-5 \ne 2[/tex]

So, we make use of:

[tex]h(x) = -\frac{1}{3}x^2 + 4[/tex]

Substitute -5 for x

[tex]h(-5) = -\frac{1}{3} * (-5)^2 + 4[/tex]

[tex]h(-5) = -\frac{1}{3} * 25 + 4[/tex]

[tex]h(-5) = -\frac{25}{3} + 4[/tex]

Take LCM

[tex]h(-5) = \frac{-25+12}{3}[/tex]

[tex]h(-5) = -\frac{13}{3}[/tex]

Calculating h(2)

This implies that: x = 2

[tex]2 = 2[/tex]

So, we make use of:

[tex]h(x) = -4[/tex]

Substitute 2 for x

[tex]h(2) = -4[/tex]

Use the above explanation to answer your question